Aísthesis e teoria da percepção no Teeteto - Silva, Daniel Reis Lima Mendes da (2012)
In this thesis, we investigate in the first part of the Theaetetus how Plato develops the concept of aísthesis, demonstrating that at first he alternates it between the senses of mental perception and bodily sensation, and finally fixed it as mere passive reception of data from the five senses. This definition has as its objective, unlink it from the character of opinion, that Protagoras associated to the term, while inserting it into the size of the sensible world, whose key feature is the constant change. From this viewpoint, we investigate the centrality of the sense of aísthesis within the theory of perception shown in the secret doctrine, in this dialogue, which in our view, would be a first attempt of Plato to a descriptive theory of perception that explains how we capture sensitive data by through the soul, accepting shares in an effort dialectical thesis of Protagoras and Heraclitus. We also analyze the link between the theories of Theaetetus, Protagoras and Heraclitus exposed in this first part of the dialogue, and how they interrelate in order to make clear that Plato maintains intact his Theory of Forms.